Keloid and Hypertrophic Scar Formation, Prevention, and Management: Standard Review of Abnormal Scarring in Orthopaedic Surgery. Issue 10 (15th May 2020) - Grabowski, Gregory; Pacana, Matthew J.; Chen, Elliot
Abstract : Keloid and hypertrophic scar formation after orthopaedic surgical closure is a complex issue. The nature and location of procedures maximize wound tension, leave foreign bodies, and diminish dermal supply, all potentiating keloid formation. There is little discussion regarding the pathophysiology and management of this recurrent problem in orthopaedic literature. Keloid formation is a fibroproliferative disorder resulting in extensive production of extracellular matrix and collagen, but prevention and treatment is poorly understood. Patient and surgical factors contributing to the development of this condition are discussed. The treatments include both medical and surgical therapies that work at a biologic level and attempt to produce a cosmetic and complication-free management strategy. Medical options that have been investigated include combinations of intralesional steroid therapy, laser therapy, and biologics. Preventive surgical closure and excision remain mainstays of treatment. Radiation therapy has also been used in refractory cases with mixed results. Despite medical therapies and surgical excision aimed at treating the resulting scar, recurrence rate is very high for all modalities that have been studied to this point. Future work is being done to better understand the pathophysiology leading to keloid and hypertrophic scar formation in an effort to find preventive methods as compared to treatment strategies.